Evaluation of Selenium Source on Nursery Pig Growth Performance, Serum and Tissue Selenium Concentrations, and Serum Antioxidant Status - Zhong-Xing Rao; Mike D. Tokach; Jason C. Woodworth; Joel M DeRouchey; Robert D. Goodband; Michele De Marco; Steven Moreland; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 3,888 pigs (337 × 1050, PIC; initially 13.1 ± 0.10 lb) were used in a 42-d trial. At the time of placement, pens of pigs were weighed and allotted to 1 of 3 dietary treatments in a randomized complete block design with blocking structure including sow farm origin, date of entry into the facility, and average pen body weight. A total of 144 pens were used with 72 double-sided 5-hole stainless steel fence line feeders, with feeder serving as the experimental unit. For each feeder, 1 pen contained 27 gilts and 1 pen contained 27 barrows. There were 24 replicates per dietary treatment. Diets were fed in three phases and all contained 0.3 ppm added selenium. A common phase 1 diet contained added selenium from sodium selenite and was fed in pelleted form to all pigs for approximately 7 d. Three selenium sources [sodium selenite; selenium yeast; and hydroxy-selenomethionine (OH-SeMet)] were used to formulate 3 experimental diets in meal form for phase 2 and phase 3. From d 0 to 7, there was marginally significant evidence (P= 0.097) of a difference in ADFI, although no significant pairwise differences were observed (P>0.05). There were no additional differences in growth performance between treatments during the d 0 to 7 period. Clinical disease attributed toStreptococcus suiswas observed within the trial, and water soluble antimicrobial therapy was administered to all treatment groups. From d 7 to 42, pigs fed OH-SeMet tended to have decreased ADG (P<0.10) and had increased (P<0.05) serum and tissue selenium concentration compared to other treatments. There was marginally significant evidence of a source × day interaction for T-AOC where the numerical increase over time was less for the OH-SeMet compared to sodium selenite or selenium yeast treatments. There was no difference (P>0.05) in antioxidant status as measured by serum GSH-Px or TBARS assay between treatments. In summary, compared to sodium selenite and selenium yeast, OH-SeMet had greater bioavailability as indicated by increased serum and tissue selenium concentration; however, antioxidant status was similar between treatments, and OH-SeMet tended to reduce growth performance compared with pigs fed sodium selenite.
Keywords: antioxidant status; growth; nursery pigs; selenium